Bombus burmensis replaces B. malaisei (Skorikov). Issue 45 (10th December 2019) - Williams, Paul H.
ABSTRACT: The name malaisei (Skorikov, 1937) is a secondary junior homonym in the genus Bombus of the name malaisei Bischoff, 1930. The name burmensis nom. nov. is proposed as a replacement name for malaisei (Skorikov, 1937), of which it is an objective junior synonym, to avoid confusion of these taxa. http://www.zoobank.org/urn:lsid:zoobank.org:pub:9F5F0037-44C5-41BC-816F-2D3BB836B6ED